Co-constructing the victim in counseling sessions for couples at the Women's Police Station: a microethnographic study - Dornelles, Clara Zeni Camargo (2000)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente.